Comparing the virtual and face-to-face speech therapy services for children and the access to these services during the COVID-19 pandemic: a scoping review - hassanati, fatemeh; mowsoon, hoda; soleimani, farin; takafolli, marzieh; Vameghi, Meroe; nobakht, zahra (Iranian Journal of Child Neurology, 2023)
Objectives There has been increased interest in using telepractice in clinical services during COVID-19. Using telepractice is little known in speech and language therapy. However, the parents and speech therapists were satisfied with this method. Therefore, this scoping review aims to compare tele speech therapy and face-to-face speech therapy during the COVID-19 pandemic and determine the efficacy of available telepractices in speech therapy. Materials & Methods This scoping review was according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) guideline. The authors systematically searched Web of Science, PubMed, and Scopus databases with specific eligibility criteria. The eligibility criteria were studies published from 1 January 2020 to 10 May 2023 from a peer-reviewed journal and written in English. In addition, the articles were about speech therapy in children during COVID-19. Results Fifteen articles were included in this scoping review. Results showed that approximately all speech therapists used tele practice during the pandemic. Parents and students are satisfied with this method but have problems with it. On the other hand, some parents and SLPs preferred tele practice accompanied by face-to-face intervention. Furthermore, few studies determined the efficacy of tele practice with clear structural methods in specific populations. Conclusion Although tele speech therapy is acceptable for providing speech and language therapy services to children with swallowing and communication disorder, speech-language therapists should increase their information and technology to achieve successful results Moreover, parents must play an essential role in telepractice services to facilitate effective communication between clinicians and families.